Поезія Тараса Шевченка в українській музиці: імена і жанри - Костюк, Н. (Студії мистецтвознавчі, 2008)
The article gives an overlook of Ukrainian composers’ creative work on the basis of Taras Shevchenko’s creativity as well as esthetic, semantic influence of folk and professional music on poetic Taras Shevchenko’s reflections directly.